Filling the Hole in Indonesiaâs Constitutional System: Constitutional Courts and the Review of Regulations in a Split Jurisdiction - Lindsey, Tim (The Constitutional Court of the Republic of Indonesia, 2018)
The Indonesian constitutional system contains a serious flaw that means that the constitutionality of a large number of laws cannot be determined by any court. Although the jurisdiction for the judicial review of laws is split between the Constitutional Court and the Supreme Court, neither can review the constitutionality of subordinate regulations. This is problematic because in Indonesia the real substance of statutes is often found in implementing regulations, of which there are very many. This paper argues that that is open to the Constitutional Court to reconsider its position on review of regulations in order to remedy this problem. It could do so by interpreting its power of judicial review of statutes to extend to laws below the level of statutes. The paper begins with a brief account of how Indonesia came to have a system of judicial constitutional review that is restricted to statutes. It then examines the experience of South Koreaâs Constitutional Court, a court in an Asian civil law country with a split jurisdiction for judicial review of laws like Indonesiaâs. Despite controversy, this court has been able to interpret its powers to constitutionally invalidate statutes in such a way as to extend them to subordinate regulations as well. This paper argues that Indonesiaâs Constitutional Court should follow South Koreaâs example, in order to prevent the possibility of constitutionalism being subverted by unconstitutional subordinate regulations.